2020
DOI: 10.21203/rs.3.rs-102000/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Phytochemical Index and Psychological Disorders in a large sample of Iranian adults: a population-based study

Abstract: Background: Intake of plant foods including of Phytochemicals may be decrease risk of mental health.Aim: This study aim to investigate association of Dietary Phytochemical Index)DPI( with symptoms of depression, anxiety and stress in a large sample of Iranian adults.Methods: In this cross-sectional study, a total of 7385 adult aged 20-50 years old were provided from the recruitment phase of Yazd Health Study, a population-based cohort research on Iranian adults. Food intakes were assessed via validated and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The Recommended Food Score (RFS) has also been developed to measure food derived DQ but has not been associated with anxiety severity (82). A few nutrient-derived DQIs also exist and have been negatively associated with anxiety, namely the Dietary Phytochemical index (DPI) (83,84), the Dietary Antioxidant index (7), and the Dietary Antioxidant Quality Score (DAQS) (85). Sangsefidi et al (85) observed a negative association between DAQS and anxiety in females (but not in males), a relationship that became non-significant after adjusting for body mass index.…”
Section: Other Diet Quality Indicesmentioning
confidence: 99%
“…The Recommended Food Score (RFS) has also been developed to measure food derived DQ but has not been associated with anxiety severity (82). A few nutrient-derived DQIs also exist and have been negatively associated with anxiety, namely the Dietary Phytochemical index (DPI) (83,84), the Dietary Antioxidant index (7), and the Dietary Antioxidant Quality Score (DAQS) (85). Sangsefidi et al (85) observed a negative association between DAQS and anxiety in females (but not in males), a relationship that became non-significant after adjusting for body mass index.…”
Section: Other Diet Quality Indicesmentioning
confidence: 99%